2019
DOI: 10.1101/862722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inducible cell-specific mouse models for paired epigenetic and transcriptomic studies of microglia and astroglia

Abstract: 23Epigenetic regulation of gene expression occurs in a cell type-specific manner. Current cell-type 24 specific neuroepigenetic studies rely on cell sorting methods that can alter cell phenotype and 25 introduce potential confounds. Here we demonstrate and validate a Nuclear Tagging and 26Translating Ribosome Affinity Purification (NuTRAP) approach for temporally controlled labeling 27 and isolation of ribosomes and nuclei, and thus RNA and DNA, from specific CNS cell types. 28Paired analysis of the transcript… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…A study using microglia isolated from LPStreated mice to explore the changes of IL-1β and its DNA methylation is consistent with ours [18]. Further study by using of transgenic inducible cre mouse models that allow for manipulation of speci c oxed genes, or tagging of cell-speci c nuclei/and or polysomes represent valuable research tools is needed [75]. Interestingly, we also found that global DNA methylation of dorsal hippocampus was unchanged, suggesting that perhaps DNA hypomethylation is not a global phenomenon.…”
Section: Discussionsupporting
confidence: 75%
“…A study using microglia isolated from LPStreated mice to explore the changes of IL-1β and its DNA methylation is consistent with ours [18]. Further study by using of transgenic inducible cre mouse models that allow for manipulation of speci c oxed genes, or tagging of cell-speci c nuclei/and or polysomes represent valuable research tools is needed [75]. Interestingly, we also found that global DNA methylation of dorsal hippocampus was unchanged, suggesting that perhaps DNA hypomethylation is not a global phenomenon.…”
Section: Discussionsupporting
confidence: 75%
“…Previous methods for performing INTACT and TRAP using NuTRAP mice have taken separate tissue homogenates for each procedure [28, 38]. In this study, we performed simultaneous isolation of nuclei and RNA from a single tissue homogenate containing bilateral hippocampi (referred to as “simultaneous isolations”).…”
Section: Resultsmentioning
confidence: 99%
“…Roh et al first developed the NuTRAP mouse to characterize adipocyte-specific and hepatocyte-specific epigenetic and transcriptional profiles [29]. The NuTRAP mouse has since been used to perform paired transcriptome and DNA modification analysis in astrocytes and microglia, demonstrating its utility in CNS cell-types [38]. The Emx1-NuTRAP mouse described here provides rapid, cost-effective characterization of neuron-specific changes to epigenetic state and gene expression using whole-tissue homogenates with heterogeneous cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ex vivo microglial activation has the potential of introducing confounds that may mask endogenously induced activation, such as in a pathological state. To avoid cell-isolation confounds, microglial-specific cre-lines (Cx3cr1-cre/ERT2) have been combined with various floxed ribosomal tagging models: 1) ribosome tagging (RiboTag) (Haimon et al, 2018), 2) translating ribosome affinity purification (TRAP) (Ayata et al, 2018), and 3) nuclear tagging and translating ribosome affinity purification (NuTRAP) (Chucair-Elliott et al, 2020), allowing the immunoprecipitation (IP) of tagged polysomes to isolate microglial-specific translatomes without the need for cell isolation. Although transgenic ribosome IP-approaches overcome many of the potential confounds of ex vivo activation, experimental endpoints such as proteomics and single cell heterogeneity still require cell isolation of intact microglial cells.…”
Section: Introductionmentioning
confidence: 99%